Comprehension and navigation of networked hypertexts. (29th January 2018) - Blom, Helen; Segers, Eliane; Knoors, Harry; Hermans, Daan; Verhoeven, Ludo
Abstract: This study aims to investigate secondary school students' reading comprehension and navigation of networked hypertexts with and without a graphic overview compared to linear digital texts. Additionally, it was studied whether prior knowledge, vocabulary, verbal, and visual working memory moderated the relation between text design and comprehension. Therefore, 80 first‐year secondary school students read both a linear text and a networked hypertext with and without a graphical overview. Logfiles registered their navigation. After reading the text, students answered textbased multiple choice questions and drew mindmaps to assess their structural knowledge of each text content. It was found that both textbased and structural knowledge were lower after reading a networked hypertext than a linear text, especially in students with lower levels of vocabulary. Students took generally more time to read the hypertext than the linear text. We concluded that networked hypertexts are more challenging to read than linear texts and that students may benefit from explicit training on how to read hypertexts. Lay description: What is already known about this topic: Reading comprehension of adults is lower in networked hypertexts than in linear texts. Less is known about comprehension and navigation of networked hypertexts in secondary school students. Individual skills (prior knowledge, vocabulary, verbal, and visuospatial working memory) are related to comprehension of hierarchical hypertexts. Less is known about the influence of individual skills on students' comprehension of networked hypertexts. What this paper adds: Comprehension of networked hypertexts was lower than of linear digital texts. Secondary school students took more time to read a hypertext than a linear digital text. Secondary school students with lower vocabulary particularly were negatively affected by the networked structure. Implications of study findings for practitioners: Teachers need to be aware that reading a networked hypertext is more challenging than a linear text. Explicit practice with reading a networked hypertext can be helpful for those students.